1996
DOI: 10.1093/mnras/281.4.1315
|View full text |Cite
|
Sign up to set email alerts
|

Line profile variations in   Doradus

Abstract: We present data from high-dispersion echelle spectra and simultaneous uvby photometry for γ Doradus. These data were obtained from several sites during 1994 November as part of the MUSICOS-94 campaign. The star has two closely-spaced periods of about 0.75 d and is the brightest member of a new class of variable early F-type stars. A previously suspected third period, very close to the other two, is confirmed. Previous observations indicated that sudden changes could be expected in the spectrum, but none were f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 8 publications
5
60
0
Order By: Relevance
“…From line profile variations in γ Doradus itself and using the moments method to identify the pulsational modes of the three periodic components, Balona et al (1996) Krisciunas et al (1995), Aerts & Krisciunas (1996) found with the moments method that they are a manifestation of the = 3, |m| = 1 spheroidal mode and its toroidal corrections due to the rotation of the star. Investigating two frequencies (1.32 d −1 and 1.40 d −1 ) deduced from multisite photometry of HD 108100, Breger et al (1997) concluded that amplitude ratios and phase differences between the light curves at different wavelengths are consistent with g-mode pulsation of = 1, rather than = 2.…”
Section: Comparison With Previous Mode Identifications In γ Doradus Smentioning
confidence: 99%
“…From line profile variations in γ Doradus itself and using the moments method to identify the pulsational modes of the three periodic components, Balona et al (1996) Krisciunas et al (1995), Aerts & Krisciunas (1996) found with the moments method that they are a manifestation of the = 3, |m| = 1 spheroidal mode and its toroidal corrections due to the rotation of the star. Investigating two frequencies (1.32 d −1 and 1.40 d −1 ) deduced from multisite photometry of HD 108100, Breger et al (1997) concluded that amplitude ratios and phase differences between the light curves at different wavelengths are consistent with g-mode pulsation of = 1, rather than = 2.…”
Section: Comparison With Previous Mode Identifications In γ Doradus Smentioning
confidence: 99%
“…Their discovery among field stars is almost only Send offprint requests to: S. Martín, e-mail: susana@merate.mi.astro.it achievable serendipitously and, once discovered, they need multi-longitude observing campaigns to conveniently sample their curves. Examples are the works published by Balona et al (1996), Breger et al (1997) and Zerbi et al (1999).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these minor setbacks, the γ Dor variables were defined as a class by Kaye et al (1999a) who, based on informal discussions at a conference held in 1995 at Cape Town, South Africa (Stobie & Whitelock 1995), and upon several papers in the literature (e.g., Krisciunas et al 1993;Balona et al 1996;Zerbi et al 1997aZerbi et al , 1997bPoretti et al 1997;Kaye 1998a;Kaye et al 1999b), defined the class to consist of "variable stars with an implied range in spectral type A7-F5 and in luminosity class IV, IV-V, or V; their variations are consistent with the model of high-order (n), low-degree ( ), nonradial, gravity-mode oscillations. "…”
Section: The Pastmentioning
confidence: 99%
“…While some may suspect that this is due to the intrinsically difficult nature of analysing γ Dor data, this particular issue has been verified with double-blind tests using different software and different analytical and numerical techniques on the same sets of data. Interested readers are encouraged to examine the published literature on 9 Aurigae (see, e.g., Krisciunas et al 1991;Krisciunas et al 1993;Balona, Krisciunas & Cousins 1994; Krisciunas et al 1995a;Aerts & Krisciunas 1996;Balona et al 1996;Zerbi et al 1997a); in addition, more than 10 years of BV differential photometry is now available on this object, yet the temporal dependence of the various modes is not understood.4 The "mystery" of HD 8801 and the recently discovered similar objects are discussed in the previous section. …”
mentioning
confidence: 99%
See 1 more Smart Citation